Multiplexed Host-Induced Gene Silencing of Aspergillus flavus Genes Confers Aflatoxin Resistance in Groundnut - Kalyani Prasad; Kalenahalli Yogendra; Hemalatha Sanivarapu; Kanniah Rajasekaran; Jeffrey W. Cary; Kiran K. Sharma; Pooja Bhatnagar-Mathur (Toxins, 2023)
Aflatoxins are immunosuppressive and carcinogenic secondary metabolites, produced by the filamentous ascomycete Aspergillus flavus, that are hazardous to animal and human health. In this study, we show that multiplexed host-induced gene silencing (HIGS) of Aspergillus flavus genes essential for fungal sporulation and aflatoxin production (nsdC, veA, aflR, and aflM) confers enhanced resistance to Aspergillus infection and aflatoxin contamination in groundnut (<20 ppb). Comparative proteomic analysis of contrasting groundnut genotypes (WT and near-isogenic HIGS lines) supported a better understanding of the molecular processes underlying the induced resistance and identified several groundnut metabolites that might play a significant role in resistance to Aspergillus infection and aflatoxin contamination. Fungal differentiation and pathogenicity proteins, including calmodulin, transcriptional activator-HacA, kynurenine 3-monooxygenase 2, VeA, VelC, and several aflatoxin pathway biosynthetic enzymes, were downregulated in Aspergillus infecting the HIGS lines. Additionally, in the resistant HIGS lines, a number of host resistance proteins associated with fatty acid metabolism were strongly induced, including phosphatidylinositol phosphate kinase, lysophosphatidic acyltransferase-5, palmitoyl-monogalactosyldiacylglycerol Δ-7 desaturase, ceramide kinase-related protein, sphingolipid Δ-8 desaturase, and phospholipase-D. Combined, this knowledge can be used for groundnut pre-breeding and breeding programs to provide a safe and secure food supply.